How Environmental Cost Accounting Can Transform Hospital Medical Waste Policies - Rigel Nurul Fathah; Teti Anggita Safitri (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the implementation of environmental cost management in hospital waste management using the Environmental Management Accounting (EMA) framework. In Indonesia, hospitals increasingly implement environmental management practices, yet the integration of environmental costs into formal accounting systems remains limited. This research aims to analyze how environmental costs related to medical waste management are identified, measured, and recorded in hospital accounting practices. The study adopts a qualitative single case study approach conducted at PKU Muhammadiyah Nanggulan Hospital. Data were collected through semi-structured interviews, document analysis, observations, and financial records from 2023 to 2024 and analyzed using thematic analysis. The findings indicate that the hospital has implemented several environmental management practices, including medical waste segregation, wastewater treatment through IPAL facilities, and cooperation with certified third-party waste management companies. However, environmental costs are still recorded as general operational expenses under the IPAL account, without a clear classification in line with EMA principles. Integrating EMA into hospital accounting systems could improve transparency into environmental costs, strengthen environmental accountability, and support corporate social responsibility in sustainable healthcare management.